Diagnostics in Waldenström's macroglobulinemia: a consensus statement of the European Consortium for Waldenström's Macroglobulinemia - Dogliotti, Irene; Jiménez, Cristina; Varettoni, Marzia; Talaulikar, Dipti; Bagratuni, Tina; Ferrante, Martina; Pérez, José; Drandi, Daniela; Puig, Noemí; Gilestro, Milena; García-Álvarez, María; Owen, Roger; et al. (Leukemia, 2023)
The diagnosis of Waldenström's macroglobulinemia (WM), an IgM-associated lymphoplasmacytic lymphoma, can be challenging due to the different forms of disease presentation. Furthermore, in recent years, WM has witnessed remarkable progress on the diagnostic front, as well as a deeper understanding of the disease biology, which has affected clinical practice. This, together with the increasing variety of tools and techniques available, makes it necessary to have a practical guidance for clinicians to perform the initial evaluation of patients with WM. In this paper, we present the consensus recommendations and laboratory requirements for the diagnosis of WM developed by the European Consortium of Waldenström's Macroglobulinemia (ECWM), for both clinical practice as well as the research/academical setting. We provide the procedures for multiparametric flow cytometry, fluorescence in situ hybridization and molecular tests, and with this offer guidance for a standardized diagnostic work-up and methodological workflow of patients with IgM monoclonal gammopathy of uncertain significance, asymptomatic and symptomatic WM.